Tests of racial discrimination in a simple financial market: Managers in Major League Baseball - Rodney J. Paul; Andrew P. Weinbach; Justin Mattingly (International Journal of Financial Studies, 2018)
This study tests for racial discrimination against minority managers in Major League Baseball using financial-market imbalances as it relates to the wagering marketplace for the sport. Using detailed betting data on the percentage bet on the favorite from Sports Insights, we test for prejudice against minority mangers using an ordinary least squares multiple regression model. The results reveal that bettors have a clear preference for the favored team as the percentage bet on the favorite increases with the odds on the favorite. In addition, they prefer road favorites by an even greater margin. In terms of minority managers, there is no evidence of discrimination against minorities. In fact, bettors prefer to wager on minority managers by a statistically significant margin when they are favorites. This finding suggests that either the participants in this financial marketplace are not prejudiced against minority managers or the financial incentives inherent in the market drive out discrimination against the minority managers.
Keywords: Z2; D91; 330; race; discrimination; betting markets; managers; baseball